THE COMPETENCY OF THE ACCOUNTANTS OF INDUSTRIAL FACTORIES IN NONTHABURI PROVINCES IN CHIEF ACCOUNTANTS’ OPINION - ชีวพัฒนพันธุ์, ธนิษฐา (RMUTT Global Business and Economics Review, 2015)
The objective of this research was to study and to compare the opinions of Chief Accountants in Nonthaburi Province’s Industrial Factories, on the ideal versus actual performance competencies of accountants aspects. The sample group was the Purposive Sampling which composed of 68 chief accountants working in 68 Nonthaburi province’s industrial factories. The tools used in this research were questionnaires. The reliabilities of the questionnaires was 0.85. The descriptive statistics such as percentage mean standard deviation and paired t-test were calculated in order to explain the research findings. It found that the ideal performance competencies of accountants it found that professional affection was excellent, academic knowledge and job performance were in good level. For the actual performance competencies of accountants in three aspects were in good level, led by professional affection and followed by job performance and academic knowledge, respectively. The comparison of the ideal versus actual performance competencies of accountants in academic knowledge, job performance and professional affection were discovered that the ideal performance competencies were statistically significantly higher than the actual performance competencies at .01 in all aspects.